Analisis Determinan Risiko Terhadap Indeks Fungsi Seksual pada Ibu Pascapersalinan - Luna Alfarizi; Anina Fatmawati; Santi Nawahita (Lembaga Penelitian dan Pendidikan, 2025)
The postpartum period represents a critical phase of physical and psychological adaptation for mothers, including changes in sexual function. Physiological alterations, psychological conditions, and social factors may influence the quality and satisfaction of sexual relationships after childbirth. This study aims to analyze the risk determinants associated with the sexual function index among postpartum women. An observational analytic study with a cross-sectional design was employed. The study sample consisted of mothers within 6 weeks to 6 months postpartum, selected using purposive sampling. Data were collected using the standardized Female Sexual Function Index (FSFI) questionnaire along with demographic and clinical data sheets. Bivariate analysis was conducted using the Chi-square test, while multivariate analysis employed logistic regression to identify dominant risk factors. The results showed that maternal age, parity, mode of delivery, fatigue level, and psychological conditions (including symptoms of postpartum depression) were significantly associated with FSFI scores (p < 0.05). Among these, psychological factors were identified as the most dominant determinants of decreased sexual function. These findings highlight the importance of adopting a holistic approach in postpartum care that incorporates sexual counseling, fatigue management, and mental health screening. Integrated interventions are expected to improve quality of life and intimate relationships among postpartum couples.